Discursive Power - Mickūnas, Algis (Sociologija. Mintis ir veiksmas, 2004)
The phenomenon of power is implicit in numerous critiques of modern sciences and their methods, resulting in the crisis of rationality. Our analyses will follow two intentionalities, the vertical and the horizontal, showing that the modern scientific rationality assumes principles which exclude the vertical. By “intentionality” we mean a way of experiencing the world at the exclusion of other ways. Thus, intentionality is not a private affair but can be carried from generation to generations. For example, scientists invariably will say “let us look at the world mathematically,” proposing a quantitative mode of perception over poetic, ritualistic, etc. The latter, while equally intentional, will be discarded by science. Thus the scientific conception of mathematical method, as a way of mastering the material world, intimates also a restriction of linguistic sign systems and uses to specific modes, mathematical discourse, at the expense and exclusion of other discursive forms. If not deliberate, there is a specific “bracketing” that was performed by the philosophies and sciences of the modern age that allotted the primacy of all understanding to language, and indeed to a specific language. The result of this development is manifested in the current claims by the semiotics and the deconstructionists that language or discourse is the primary power in all domains of human experience and praxis. While at first sight outlandish, this claim is well justified on the basis of most concrete analyses of modernity, with its ontology and scientific method. Our approach will trace out “bracketing” and show what phenomena become discarded and what phenomena remain in order to be constitutive of power. It is hoped that the result of this investigation will reveal specific formations which belong to no one, are nowhere, and yet comprise the very modalities of our modern awareness. What is meant here by awareness consists of specific noetic practices ruled by, and expressive of, a set of intentionalities. In addition, the noetic practices constitutive of power are also ruled by a specific form of transcendence lending such practices their autonomy. The latter is expressed in numerous ways across various socio-political, economic and scientific formations, aims, and imageries. It lends an appearance of a total transcendental arbitrariness to the noetic practices at all levels. The phrase “noetic practices” encompasses what the human actually does in relationship to the world of objects of whatever type and at whatever level of posited objectivity.